Thomas Wolfe: Modo and the Potential for Renaissance - Amélie Moisy (Sillages Critiques)
In Thomas Clayton Wolfe (1900-1938) and his work, the Modernist tension between neophilia and neophobia was apparent and ultimately redirected into a restoration of vital force of writing. He felt that the American writer had to uncover the new, to “learn to speak the tongue that no one in this land has spoken yet.” Yet he drew inspiration from the classical and European literature of the past while experimenting with Modernist techniques and themes, as he sought permanence in a changing world. He was associated with writers of the various “renaissances” – the English Renaissance, the American Renaissance, and more particularly the Southern Renaissance. The ambient “neophilia” and “neophobia” caused his work to be viewed as both virtuous and unfortunate – “bad Modernism,” to use Douglas Mao and Rebecca Walkowitz’s term for daring art which becomes imperiled when it achieves wide acceptance. To Wolfe’s conservative publishers, his excessive and emotionally intense style, running the gamut between lyrical and terse, seemed cutting edge. Yet his professional associations affected his radically independent image and his contemporaries; the Southern Agrarians, who became the New Critics, rejected his artistic choices. Central to Modernism is the tension between Wolfe’s preoccupation with degeneration and decay and his emphasis on the modo, or “just now,” the fraught, often glorious fleeting instant. Wolfe recreates the moments of intensity Pater called for in his Conclusion to “The Renaissance” both in the poetry of his prose and in the political “conversions” he describes. The modo contains neophilia and neophobia and dispels them through a feeling of rightness and communion; it makes Wolfe’s work exceptionally dynamic for it heralds a vita nova.